PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP LABA PADA PT. MEGAMITRA MAKMUR SENTOSA MANADO - Laki, Melisa Feronica; Nangoi, Grace B.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Promotion costs and distribution costs are very beneficial in increasing company profits. This study aims to determine the promotion costs and distribution costs on profits. The study was conducted at PT Megamitra Makmur Sentosa Manado. This research is a quantitative descriptive research. The sample in the study were promotion costs, distribution costs and profit at PT Megamitra Makmur Sentosa Manado in 2010-2016. Data was obtained using documentation and interview methods. Then all data were analyzed using stastistic (multiple linear analysis) with the help of SPSS. The results of this study indicate that the significance value generated by the promotion cost variable (X1) is 0,000 which means <0.05, it can be concluded that the promotion cost variable (X1) has a positive significant effect on the profit variable (Y). Significant value of distribution costs (X2) that is equal to 0,000 which means <0.05. individually distribution costs (X2) have a negative significant effect on the profit variable (Y).